2017
DOI: 10.1080/14759551.2017.1386189
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal accomplishment of alignment and affiliation in the local space of distant meetings

Abstract: Technology-mediated (i.e. distant) meetings are complex settings that involve distributed participation frameworks and the coordination of actions in multiple interactional spaces (cf. Mondada 2013). This paper examines how problems with hearing, speaking, or understanding in the overall meeting space enable the negotiation of alignment and affiliation by co-present participants in the same local meeting space. Conversation Analysis (CA) is used to investigate the local accomplishment of alignment and affili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 51 publications
0
13
0
1
Order By: Relevance
“…An affiliating response would not be conditionally relevant. Expanding on this observation, and paraphrasing Oittinen (2018: 34), we note that alignment is about supporting the action/turn-in-progress, establishing mutual understanding (intersubjectivity) and accepting identities made relevant in the talk (e.g. speaker/hearer, chair/participants, manager/subordinate and (authentic) leader/follower).…”
Section: Method: Interactional Analysis Of Leadershipmentioning
confidence: 67%
“…An affiliating response would not be conditionally relevant. Expanding on this observation, and paraphrasing Oittinen (2018: 34), we note that alignment is about supporting the action/turn-in-progress, establishing mutual understanding (intersubjectivity) and accepting identities made relevant in the talk (e.g. speaker/hearer, chair/participants, manager/subordinate and (authentic) leader/follower).…”
Section: Method: Interactional Analysis Of Leadershipmentioning
confidence: 67%
“…Studies such as these underline the importance of attending to multimodality when exploring social interaction and social phenomena. Particularly relevant for this paper, are studies that explore multimodal aspects of the accomplishment of workplace activities in, for example, medical environments (LeBaron et al., 2016; Mondada, 2007), the transport industry (Nevile, 2007; Nevile and Wagner, 2016), and corporate meetings (Asmuß and Oshima, 2012; Mortensen, 2013; Mortensen and Lundsgaard, 2011; Oittinen, 2018). Finally, we draw on the study by Van de Mieroop et al.…”
Section: Methodsmentioning
confidence: 99%
“…Further, although ICT makes work interaction possible for geographically distributed teams (Klitmøller and Lauring, 2013), research has demonstrated that mediation with ICT in itself adds complexity to the accomplishments of social interaction (Heath et al, 2000). This is because, on account of the lack, or limited use, of body cues, gaze, delay in minimal response, and so on (Kangasharju, 1996;Oittinen, 2018), technological mediation restricts virtual interaction. This consequently complicates the co-production of meaningful interaction in virtual contexts.…”
Section: Virtual Interactionmentioning
confidence: 99%
“…Participants may distribute their attention across physical and virtual spaces in technology-rich environments [30]. This study focuses on what can be characterized as a local space [49], the school classroom where the design work among the school pupils takes place. In the context of school, the architecture of the building and design of objects derive from actors spatially and temporally more distant.…”
Section: Categorizing Humormentioning
confidence: 99%
“…When working with children in school context we encourage researchers and practitioners to understand and appreciate the classroom as a complex microcosmos: as a multifaceted constellation of people, objects, tools, relationships, discourses, as a stage with particular performances (see also e.g. [14,39,49,54,55]. A design project is not a spatially and temporally isolated unit.…”
Section: Implications Of the Studymentioning
confidence: 99%